Evaluation of shallow ground water recharge and its potential for dry season irrigation at Brante Watershed, Dangila, Ethiopia - Eshete, D. G.; Tilahun, Seifu A.; Moges, M. A.; Schmitter, Petra S.; Dokou, Z.; Sinshaw, B. G.; Atalay, E. B.; Takele, D. Y.; Getie, W. A. (Springer, 2020)
The estimation of crop water demand and understanding groundwater use is an essential component for managing water effectively. Groundwater is the main source of irrigation in Dangila. However, there is a lack of information in the study area on amount of irrigated land, irrigation water use and demand, groundwater recharge. Consequently, the objective of this study is to determine the groundwater recharge and its potential for dry season irrigation. The study was conducted in Brante watershed of 5678 ha located in Dangila woreda, Ethiopia. Water table data from twenty-five wells and discharge data at the outlet of the watershed used to assess recharge amount in 2017. To calculate irrigation water demand, CROPWAT model was used. Questionnaires were undertaken to assess groundwater use. A KOMPSAT-2 image was used to map shallow groundwater irrigated vegetables in February 2017. From the soil water balance method, the annual groundwater recharge was 17,717,690 m3 which is 15.8% of annual rainfall, and recharge amount of 14,853,339 m3 was obtained using water table fluctuation method. From satellite image classification the area coverage of dry season irrigated vegetables (onion, tomato, pepper) below the main road was 4.02 ha. From CROPWAT result, seasonal irrigation water demand for onion, Tomato, and pepper was 333,314, and 261 mm respectively. However, the questioners result indicates that farmers apply in average 20% more water than crop water demand. In the watershed 60,150 m3, 62,750 m3 and 41,603 m3 of water was abstracted for irrigation, domestic and livestock use respectively. The ratio of groundwater use to groundwater recharge at the watershed scale was found to be only 1%. This study indicates that the current use of groundwater was sustainable. For better improvement of household livelihood irrigation can be further expand using ground water. Future work should be performed to determine if the method outlined in this research could be used to accurately estimate available water potential.